Creep and Recovery Behavior of Continuous Fiber-Reinforced 3DP Composites - Ans Al Rashid (14777050) (2021)
The commercial availability of 3D printers for continuous fiber-reinforced 3D-printed (CFR3DP) composites has attracted researchers to evaluate the thermomechanical properties of these materials. The improvement of strength through chopped or continuous fiber reinforcements in polymers could provide remarkable results, and its exploration can provide broad applications in several industries. The evaluation of mechanical properties of these materials at elevated temperatures is vital for their utilization in severe operating conditions. This study provides insight into the effect of different fiber reinforcements (Kevlar, fiberglass, and high-strength high-temperature fiberglass) and temperatures on the creep and recovery behavior of CFR3DP Onyx composites. Experimental results were also compared with analytical models, i.e., Burger’s model and Weibull distribution function, for creep and recovery. Results from analytical models agreed well with experimental results for all the materials and temperatures. A significant drop in maximum and residual strains was observed due to the introduction of fibers. However, the creep resistance of all the materials was affected at higher temperatures. Minimum creep strain was observed for Onyx-FG at 120 °C; however, at the same temperature, the minimum residual strain was observed for Onyx-KF. Based on the analytical models and experimental results, the role of fiber reinforcements on the improvement of creep and recovery performance is also discussed. Other Information Published in: Polymers License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.3390/polym13101644